Rancang Bangun Website Pengelolaan Sistem Informasi Osis Dan Ekstrakurikuler di SMAN 1 Pandih Batu: Website Design For Osis Andextracurricular Information System Management In Public High School 1 Pandih Batu - Miftahurrizqi Miftahurrizqi; M. Haris Qamaruzaman; Jamaliansyah (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2023)
Pandih Batu 1 Public High School, is one of the State Senior High Schools in Pandih Batu District, Pulang Pisau Regency, Central Kalimantan, to be precise on Jl. Pemdinding Desa Pangkoh Hulu. So far, the activities carried out by the OSIS as well as extracurricular activities at Pandih Batu 1 Public High School are still managed manually, such as in the election of new OSIS chair candidates at Pandih Batu 1 Public High School still using conventional methods, namely direct voting, do not take advantage of information technology. In overcoming these problems, the author intends to build an information system for the management of the Pandih Batu 1 State Senior High School student council called SI-OSIS. The title that will be raised by the author in this final project research is "Design and Build a Website Management of Student Council Information Systems and Extracurriculars at Pandih Batu 1 Public High School" with the hope that it will become a new tool and alternative that can facilitate the management of Pandih Batu 1 Public High School Student Council to become more sophisticated in the era of information technology that has been digitized so that students at SMA Negeri 1 Pandih Batu are not left behind with current information technology developments. The data collection methods used by the author are observation, interviews, and library research. Pandih Batu 1 Public High School, is one of the State Senior High Schools in Pandih Batu District, Pulang Pisau Regency, Central Kalimantan, to be precise on Jl. Pemdinding Desa Pangkoh Hulu. So far, the activities carried out by the OSIS as well as extracurricular activities at Pandih Batu 1 Public High School are still managed manually, such as in the election of new OSIS chair candidates at Pandih Batu 1 Public High School still using conventional methods, namely direct voting, do not take advantage of information technology. In overcoming these problems, the author intends to build an information system for the management of the Pandih Batu 1 State Senior High School student council called SI-OSIS. The title that will be raised by the author in this final project research is "Design and Build a Website Management of Student Council Information Systems and Extracurriculars at Pandih Batu 1 Public High School" with the hope that it will become a new tool and alternative that can facilitate the management of Pandih Batu 1 Public High School Student Council to become more sophisticated in the era of information technology that has been digitized so that students at SMA Negeri 1 Pandih Batu are not left behind with current information technology developments. The data collection methods used by the author are observation, interviews, and library research.